High-Titer Methane from Organosolv-Pretreated Spruce and Birch - Leonidas Matsakas; Christos Nitsos; Dimitrij Vörös; Ulrika Rova; Paul Christakopoulos (Energies, 2017)
The negative impact of fossil fuels and the increased demand for renewable energy sources has led to the use of novel raw material sources. Lignocellulosic biomass could serve as a possible raw material for anaerobic digestion and production of biogas. This work is aimed at using forest biomass, both softwood (spruce) and hardwood (birch), as a raw material for anaerobic digestion. We examined the effect of different operational conditions for the organosolv pretreatment (ethanol content, duration of treatment, and addition of acid catalyst) on the methane yield. In addition, we investigated the effect of addition of cellulolytic enzymes during the digestion. We found that inclusion of an acid catalyst during organosolv pretreatment improved the yields from spruce, but it did not affect the yields from birch. Shorter duration of treatment was advantageous with both materials. Methane yields from spruce were higher with lower ethanol content whereas higher ethanol content was more beneficial for birch. The highest yields obtained were 185 mL CH4/g VS from spruce and 259.9 mL CH4/g VS from birch. Addition of cellulolytic enzymes improved these yields to 266.6 mL CH4/g VS and 284.2 mL CH4/g VS, respectively.